A trajetória da educação rural no Paraná: das escolas rurais às escolas do campo (1961 a 2006) - Leske, Gilson (2014)
The research proposes to develop a study on the historical trajectory of rural education in Parana, focuses on investigating the preparation of the proposal of rural Education, which is emerging from a series of discussions, reflections and struggles, mainly promoted by social movements connected to the field. In this perspective the field education identity has been built with reflections from a social practice. We problematize the institutionalization of this type of education from a historical study of the Brazilian state of Paraná and government policies, as well as the trajectory of rural education in the State of Paraná, aiming to unveil in this theoretical, political and ideological issues related to this process. It became necessary to investigate the historical background of the struggle of social movements for land reform and land established over the years in our country, which highlights antagonisms that pervade the Brazilian agrarian structure for centuries, generating political conflicts between the peasantry and landowning. In this historical context, emerges from the social movements the fighting for new demands, among them the construction of an educational proposal that meets the desires organized as social class, to meet the specifities of the field, which differs from the rural education to be developed during the movement itself. The survey was conducted by analysis of documentary sources, such as the Law of Guidelines and Bases of Education; Curriculum Guidelines of Field Education; decrees; Opinions and other sources the Secretary of State of Paraná Education, the sources of the Secretary of Agriculture of Paraná and documents of Landless Workers Movement, besides others which are made relevant during the development of this work. We also use the literature review, theoretical basis for questioning and the object of study.